Bioactive Molecules and Their Mechanisms of Action - Wang, Dongdong; Heiss, Elke; Šmejkal, Karel; Atanasov, Atanas G (Molecules, 2019)
Chronic inflammation with a wide spectrum of connected diseases (e [...].
Keywords: tradiční čínská medicína; Animals; Inflammation; Signal Transduction; regulace genové exprese; lidé; zánět; fytonutrienty; zvířata; Gene Expression Regulation; Medicine, Chinese Traditional; Phytochemicals; objevování léků; signální transdukce; Drug Discovery; Humans